Computational Modeling of Microstructure and Numerical Analysis of Stress-Strain States of Cast Iron with Vermicular Graphite Shape. (2016) - Bezdedová, Radka; Kováčiková, Petra; Vavro, Ján; Vavro, Ján
Abstract: Nowadays the modern computational methods depend on the creation of a virtual model and subsequent simulation. The report deals with the analysis of stress conditions on microstructure of cast iron with vermicular graphite type. It discusses the chemical composition, mechanical properties and structure that we will serve as input parameters for computational modelling and numerical analysis. The computational model structure was created two-dimensional by linear triangular elements. The size of elements was determined based on sensitivity analysis. According to the real structure of cast iron with vermicular graphite shape will be created model, from which will be performed numerical analysis of voltage-strain states in finite element software system ADINA 8.8.0. For the purpose of calculation and subsequent statistical evaluation of the results in the future will be necessary to generate much more of geometric models.